2004
DOI: 10.1016/j.bbrc.2004.09.168
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “Potent and selective inhibition of SARS coronavirus replication by aurintricarboxylic acid” [Biochem. Biophys. Res. Commun. 320 (2004) 1199–1203]

Abstract: publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses in any form or by any means with acknowledgement of the original source. These permissions are granted for free by Elsevier for as long as the COVID-19 resource centre remains active. ErratumErratum to ''Potent and selective inhibition of SARS coronavirus replication by aurintricarboxylic acid'' [Biochem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One such compound found to show antiviral activity was aurintricarboxylic acid (ATA; Figure ). ATA is an anionic polymer shown to bind to a variety of protein targets, including gp120 of HIV‐1 and HIV‐2, that has been demonstrated to prevent SARS‐CoV replication (IC 50 =0.2 mg mL −1 ) . Despite computational models validated against known ATA targets predicting RdRp as the bound target, no experimental evidence has demonstrated this relationship .…”
Section: Rna‐dependent Rna Polymerasementioning
confidence: 99%
“…One such compound found to show antiviral activity was aurintricarboxylic acid (ATA; Figure ). ATA is an anionic polymer shown to bind to a variety of protein targets, including gp120 of HIV‐1 and HIV‐2, that has been demonstrated to prevent SARS‐CoV replication (IC 50 =0.2 mg mL −1 ) . Despite computational models validated against known ATA targets predicting RdRp as the bound target, no experimental evidence has demonstrated this relationship .…”
Section: Rna‐dependent Rna Polymerasementioning
confidence: 99%
“…The same study also reported that ATA bind to the catalytic domain of RdRp in severe acute respiratory syndrome (SARS) coronavirus [17,18]. The same study also reported that ATA bind to the catalytic domain of RdRp in severe acute respiratory syndrome (SARS) coronavirus [17,18].…”
Section: Introductionmentioning
confidence: 70%
“…The fluorescence was quenched with increasing concentration of ATA indicating the association of reverse transcriptase with ATA as shown in Fig. Anti-viral activity of ATA was reported due to its ability to bind several viral proteins like RNA-dependent RNA polymerase (RdRp), S1, HIV integrase and likely to alter their functions [17,18]. The dissociation constant (K d = 0.255 M) was calculated from the double-reciprocal plot as shown inset in Fig.…”
Section: Reverse Transcriptase Activity Was Inhibited By Atamentioning
confidence: 98%
“…Recently, He et al discovered that ATA (39) selectively inhibits SARS-CoV replication with an IC 50 value of 454 µM and when compared to 5000 IUmL -1 of interferon α and β, ATA was about 10 times more potent than interferon α and 100 times more potent than interferon β for anti-SARS-CoV activities [85]. Protein structural studies were performed to investigate the potential binding modes/sites of ATA onto SARS-CoV RdRp, and the binding towards other pathogenic positive-strand RNA viruses, Ca 2+ -activated neutral protease (m-calpain), protein tyrosine phosphatase (PTP), HIV integrase as well as other proteins in SARS-CoV [86].…”
Section: Rna-dependent Rna Polymerase (Rdrp) Inhibitormentioning
confidence: 98%